Bogie Steering System Improving Alignment of the Urban Railway Vehicle in a Track - PODOLSKI, Michał; SŁABUSZEWSKI, Maciej; FIRLIK, Bartosz; STAŚKIEWICZ, Tomasz (Engineering Transactions, 2018)
Urban rail systems are characterized by low-radius curves which are very problematic to negotiate for modern rail vehicles. There are several inventions developed throughout time to cope with that problem. One group of them are bogie steering systems, responsible for the improvement of the alignment of carbodies in a curve, increasing ride comfort and reducing wheel and rail wear. The principle of those systems is to correct the relative settlement of bogies and carbodies during curve negotiations, to lower the angle of attack. One of such systems is described in this paper in terms of design, operation and verification. Some experimental and simulation results are presented and discussed.